1996
DOI: 10.1161/01.cir.93.10.1788
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Usage of T-Cell Receptor Vα-Vβ Genes in Infiltrating Cells in Aortic Tissue of Patients With Takayasu’s Arteritis

Abstract: The restricted usage of TCR Valpha as well as Vbeta genes by infiltrating T cells in Takayasu's arteritis may indicate that a specific antigen in the aortic tissue was targeted. Our findings provide the evidence that distinct immunological mechanisms are involved in the pathogenesis of Takayasu's arteritis and atherosclerotic aortic aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 5 publications
6
44
0
4
Order By: Relevance
“…58 Serum levels of IL-6 have also been shown to correlate with disease activity. 59 Abisror et al have done a review of the existing literature by pooling 44 adult TA patients on tocilizumab (TCZ) with the majority receiving 8 mg/kg/month.…”
Section: Biological Therapy In Tamentioning
confidence: 99%
“…58 Serum levels of IL-6 have also been shown to correlate with disease activity. 59 Abisror et al have done a review of the existing literature by pooling 44 adult TA patients on tocilizumab (TCZ) with the majority receiving 8 mg/kg/month.…”
Section: Biological Therapy In Tamentioning
confidence: 99%
“…On the other hand, strong expression of IL-6 has been shown to occur in the aortic tissue of patients with TA (6). Serum IL-6 levels have been reported to be greatly elevated in patients with TA and to correlate positively with disease activity (4,6,7).…”
mentioning
confidence: 99%
“…To investigate the roles of αβ T-cells in the immunopathology in Takayasu arteritis, especially to determine whether αβ T-cells specifically infiltrated the aortic tissue, we analyzed TCR Vα and Vβ gene usage in infiltrating cells in the aortic tissue with Takayasu arteritis as well as atherosclerotic aortic aneurysm by a reverse transcription-polymerase chain reaction (RT-PCR) method. 25) We found that almost all TCR Vα as well as Vβ genes were expressed in peripheral blood lymphocytes with Takayasu arteritis and in infiltrating cells in the aortic tissue with atherosclerotic aortic aneurysm. In sharp contrast, only a few or limited number of Vα as well as Vβ genes were preferentially rearranged and transcribed in infiltrating cells in the aortic tissue with Takayasu arteritis.…”
Section: Roles Of αβ T-cells In the Immunopathology In Takayasu Artermentioning
confidence: 77%
“…presented by HLAs may occur, as we previously reported. 8,25) The expression of HSP-65 in vascular (smooth muscle) cells may play a role in the induction of MICA expression. It seems that γδ T-cells (unlike αβ T-cells) recognize small nonpeptidic antigens without antigen processing and presentation.…”
Section: Roles Of Genetic Factors In the Immunopathology In Takayasu mentioning
confidence: 99%